2015
DOI: 10.4067/s0717-95022015000200034
|View full text |Cite
|
Sign up to set email alerts
|

A new Morphological Classification of the Anterior Inferior Iliac Spine: Relevance in Subspine Hip Impingement

Abstract: MORALES-AVALOSSUMMARY: Femoroacetabular impingement syndrome (FAI) is a clinical entity that has been recognized in recent years as a frequent cause of pain and the early development of hip arthrosis. Subspine hip impingement is characterized by the prominent or abnormal morphology of the anteroinferior iliac spine (AIIS), which contributes to the development of a clinical picture that is similar to FAI. The aims of this study were to propose a new morphological classification of the AIIS, to determine the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…140 Because most patients have articular pathology, it is difficult to recognize if the symptoms are related to EAI or purely to FAI. According to AIIS morphology, it can be divided into different types 141,142 : type I, usually of normal morphology, with a notch or contact surface between the AIIS and the acetabular rim; type II when the AIIS extends to the level of the rim, with a flat surface (type IIa) or convex surface (type IIb); and type III when the AIIS extends distally to the acetabular rim. Hetsroni and colleagues correlated these three types with different restrictions of ROM.…”
Section: Subspine Impingementmentioning
confidence: 99%
“…140 Because most patients have articular pathology, it is difficult to recognize if the symptoms are related to EAI or purely to FAI. According to AIIS morphology, it can be divided into different types 141,142 : type I, usually of normal morphology, with a notch or contact surface between the AIIS and the acetabular rim; type II when the AIIS extends to the level of the rim, with a flat surface (type IIa) or convex surface (type IIb); and type III when the AIIS extends distally to the acetabular rim. Hetsroni and colleagues correlated these three types with different restrictions of ROM.…”
Section: Subspine Impingementmentioning
confidence: 99%
“…the concave nature of the ilium wall provides recessed space for soft tissue recoil when under compression during flexion, adduction and internal rotation of the hip 4,10,11 . Amar et al reviewed 50 CT scans of 50 patients (100 hips) without hip pathology to investigate the size, position and location of the normal AIIS.…”
Section: Anterior Inferior Iliac Spine (Aiis) and Subspine Hip Impingementmentioning
confidence: 99%
“…Anatomical studies have demonstrated considerable variability in the morphology and location of the AIIS in the absence of previous trauma or avulsion 4,10 . Traction hypertrophy may result from the repeated strain placed across the AIIS from the attachment of the direct head of rectus femoris during running, cutting and kicking sports (especially during the adolescent development years); a bony response to the traction stimulus producing thickening and prominence of the AIIS which may lead to restriction of hip motion and femoro-acetabular impingement (Figure 2) 3,5 . Other congenital and developmental abnormalities of the AIIS have been described including the "Pelvic digit or pelvic rib"; this is considered to arise from a congenital abnormality during embryonic bone development and has been reported in a number of regions around the pelvis 33 including the sacrum 35 , the ilium (Iliac rib) 36 , coccyx 37 , and ischium.…”
Section: Developmental Aiis Abnormalitiesmentioning
confidence: 99%
“…Among them, the latter two types are usually related to SSI symptoms. Type II was further divided into Type IIA and Type IIB according to whether the AIIS protruded forward [ 11 ]. However, an increasing number of studies have suggested that symptomatic subspine impingement does not completely depend on AIIS morphology.…”
Section: Introductionmentioning
confidence: 99%